PENGARUH ETOS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. COZY MULTI ESTETIKA JAKARTA BARAT - Yovanka Annissa Putri Gunawan; Ahmad Syukri (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the effect of Work Ethic and Work Discipline on Employee Performance at CV. Cozy Multi Estetika, West Jakarta. The method used is descriptive quantitative. The sampling technique employs the  formula, resulting in a sample size of 60 respondents. Data analysis includes validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results of this study indicate that work ethic has a significant effect on employee performance with a determination coefficient of 41%, and hypothesis testing shows t-count > t-table (9.913 > 2.001). Work discipline also significantly affects employee performance with a determination coefficient of 39.8%, and hypothesis testing shows t-count > t-table (7.144 > 2.001). Simultaneously, work ethic and work discipline have a significant effect on employee performance, with the regression equation Y = 6.781 + 0.363X1 + 0.492X2. The determination coefficient value is 36%, while the remaining 64% is influenced by other factors. Hypothesis testing shows F-count > F-table (38.898 > 3.153).